2010
DOI: 10.1186/1475-2875-9-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity among Plasmodium falciparum field isolates in Pakistan measured with PCR genotyping of the merozoite surface protein 1 and 2

Abstract: BackgroundThe genetic diversity of Plasmodium falciparum has been extensively studied in various parts of the world. However, limited data are available from Pakistan. This study aimed to establish molecular characterization of P. falciparum field isolates in Pakistan measured with two highly polymorphic genetic markers, i.e. the merozoite surface protein 1 (msp-1)and 2 (msp-2).MethodsBetween October 2005 and October 2007, 244 blood samples from patients with symptomatic blood-slide confirmed P. falciparum mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
196
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(227 citation statements)
references
References 24 publications
22
196
8
Order By: Relevance
“…These findings are similar to the previous reports from Pakistan, India, Yemen, and sub-Saharan African countries. 10,11,16,25 A topography-based variation in the distribution of msp1, msp2, and glurp allelic families within the same area was described in previous studies, 8,10,16 which corroborates the finding of variations in allelic families in CHT and non-CHT areas in this study. Though the findings are corroborated by previous studies, in this study no significant differences were observed in the distribution of clones between the CHT and the non-CHT sample groups except for clones of 3D7/IC allelic family of msp2.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…These findings are similar to the previous reports from Pakistan, India, Yemen, and sub-Saharan African countries. 10,11,16,25 A topography-based variation in the distribution of msp1, msp2, and glurp allelic families within the same area was described in previous studies, 8,10,16 which corroborates the finding of variations in allelic families in CHT and non-CHT areas in this study. Though the findings are corroborated by previous studies, in this study no significant differences were observed in the distribution of clones between the CHT and the non-CHT sample groups except for clones of 3D7/IC allelic family of msp2.…”
Section: Discussionsupporting
confidence: 79%
“…In southeast Asia, MOI of P. falciparum for hypoendemic regions ranges from 1.00 to 2.70. 9,16,17 A high level of heterozygosity (0.80-0.93) for all the three markers in Bangladesh was recorded in this study. This finding is higher than the heterozygosity range (0.51-0.65) reported earlier in the southeast Asia/Pacific region but quite comparable to some malaria-hyperendemic African countries (0.76-0.98).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…An endemic area is attributed to higher parasite diversity and multiple genotypes of parasites. While, in low transmission areas parasites have a limited genetic diversity with monoclonal infections (Ghanchi et al 2010).…”
Section: Introductionmentioning
confidence: 99%